Apar Tourism Village Development Strategy as an Ecotourism Attraction in Pariaman City - Nini Sriafivrina; Aldri Frinaldi (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
The purpose of this study was to determine the development of the apar tourism village as an ecotourism attraction in Pariaman City, in order to create harmony between every government organization between the city government and the provincial government in managing tourist villages to be better, safer, and more comfortable to achieve independence and community welfare. The results of this study indicate that: First, the strengths in the development of the Apar tourism village: (1) The existence of clear rules in the management of the apar tourism village, (2) the coordination towards the development of the apar village tourism, (3) the creation of the apar village tourism business. Second, Weaknesses in the development of the Apar tourism village: (1) Lack of public awareness in the development of the Apar tourism village, (2) inadequate human resources, (3) unsupported facilities and infrastructure. Third, the opportunities in the development of the Apar tourism village: (1) Realizing the apar village into independent tourism, (2) creating community welfare in optimizing the tourism potential of the apar village. Fourth, Threats in the development of the Apar tourism village: (1) The decrease in the source of income from the village original income (PAD), (2) Not yet maximized in developing the economic cooperation network of various parties. Fifth, the strategy in developing the Apar tourism village: S-O strategy, namely: (1) The existence of tourism promotion by utilizing information media, (2) Coordination of the government in providing facilities and infrastructure. The WO strategies are: (1) Government policies need to be firm in implementing a better tourist village, (2) Cooperation with the trade office in providing minimarket businesses in apar tourism villages. The ST strategy is: (1) CBT support is needed in improving tourism management in the Apar village, Pariaman city, (2) Setting up easy access for the Apar tourism village. The WT strategies are: (1) Providing training in improving the quality of existing human resources, (2) Providing ongoing socialization to the community.